Peran UMKM CV Tas Rakyat Dalam Meningkatkan Kesejahteraan Masyarakat Perspektif Ekonomi Islam Desa Ngampel - Puput Risma Dayanti; Luhur Prasetiyo (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2023)
The role of micro, small and medium enterprises is very important, because MSMEs are the largest part of the national economy and become public participation in various economic sectors. Problems in research refer to problems in people's lives, namely about improving welfare. Community welfare can be helped, one of which is with MSMEs, with the existence of MSMEs, it is possible to explore all the potential of SMEs owned, explore all economic potential, reduce poverty, and improve community welfare. So this study will discuss the role of these MSMEs in improving community welfare. In the study, the author uses qualitative approaches and types of research (field research), data collection techniques by means of interviews with existing informants such as owners and surrounding communities, observation, and documentation. The results of this study show that MSMEs CV Tas Rakyat in its role in improving the welfare of the community in Ngampel Village can absorb labor, providers of goods and services for the community, utilize regional economic resources, and advance the nation's self-image. This can have a positive impact on improving welfare which can be proven from the fulfillment of several indicators of community welfare from an Islamic economic perspective, including in terms of tawhid, fulfillment of consumption, and getting a sense of security and peace in their lives. However, in the process of improving community welfare, it will definitely be accompanied by existing constraints both from internal parties (in terms of capital, human resources, and business networks) and external parties (in terms of limited facilities and infrastructure, business climate, regional autonomy, and free trade).